Bioactivity of phenolic acids: Metabolites versus parent compounds: A review. (15th April 2015) - Heleno, Sandrina A.; Martins, Anabela; Queiroz, Maria João R.P.; Ferreira, Isabel C.F.R.
Highlights: Phenolic acids are representative molecules in the diet. After absorption, they are extensively metabolized in the organism. Glucuronidation, methylation and sulfation reactions occur in their metabolism. Glucuronated metabolites exert antioxidant action in vivo . Methylated and glucuronated derivatives increase antimicrobial and antitumor activities. Abstract: Phenolic acids are present in our diet in different foods, for example mushrooms. Due to their bioactive properties, phenolic acids are extensively studied and there is evidence of their role in disease prevention. Nevertheless, in vivo, these compounds are metabolized and circulate in the organism as glucuronated, sulphated and methylated metabolites, displaying higher or lower bioactivities. To clarify the importance of the metabolism of phenolic acids, knowledge about the bioactivity of metabolites is extremely important. In this review, chemical features, biosynthesis and bioavailability of phenolic acids are discussed, as well as the chemical and enzymatic synthesis of their metabolites. Finally, metabolite bioactive properties are compared with that of the corresponding parental compounds.